Do the energy fluxes and surface conductance of boreal coniferous forests in Europe scale with leaf area?. (13th October 2016) - Launiainen, Samuli; Katul, Gabriel G.; Kolari, Pasi; Lindroth, Anders; Lohila, Annalea; Aurela, Mika; Varlagin, Andrej; Grelle, Achim; Vesala, Timo
Abstract: Earth observing systems are now routinely used to infer leaf area index (LAI) given its significance in spatial aggregation of land surface fluxes. Whether LAI is an appropriate scaling parameter for daytime growing season energy budget, surface conductance ( G s ), water‐ and light‐use efficiency and surface–atmosphere coupling of European boreal coniferous forests was explored using eddy‐covariance (EC) energy and CO2 fluxes. The observed scaling relations were then explained using a biophysical multilayer soil–vegetation–atmosphere transfer model as well as by a bulk G s representation. The LAI variations significantly alter radiation regime, within‐canopy microclimate, sink/source distributions of CO2, H2 O and heat, and forest floor fluxes. The contribution of forest floor to ecosystem‐scale energy exchange is shown to decrease asymptotically with increased LAI, as expected. Compared with other energy budget components, dry‐canopy evapotranspiration (ET) was reasonably 'conservative' over the studied LAI range 0.5–7.0 m 2 m −2 . Both ET and G s experienced a minimum in the LAI range 1–2 m 2 m −2 caused by opposing nonproportional response of stomatally controlled transpiration and 'free' forest floor evaporation to changes in canopy density. The young forests had strongest coupling with the atmosphere while stomatal control of energy partitioning was strongest in relatively sparse (LAI ~2 m 2 m −2 ) pine stands growing on mineral soils. The data analysis and model results suggest that LAI may be an effective scaling parameter for net radiation and its partitioning but only in sparse stands (LAI <3 m 2 m −2 ). This finding emphasizes the significance of stand‐replacing disturbances on the controls of surface energy exchange. In denser forests, any LAI dependency varies with physiological traits such as light‐saturated water‐use efficiency. The results suggest that incorporating species traits and site conditions are necessary when LAI is used in upscaling energy exchanges of boreal coniferous forests.